2015
DOI: 10.1111/pbi.12317
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide analysis of small RNAs in nonembryogenic and embryogenic tissues of citrus: microRNA‐and siRNA‐mediated transcript cleavage involved in somatic embryogenesis

Abstract: SummarySomatic embryogenesis (SE) is a process of somatic cells becoming dedifferentiated and generating embryos. SE has been widely used in biotechnology as a powerful way of regeneration and a model system for studying plant embryogenesis, but the controlling mechanisms of SE are far from clear. Here, we show the genomewide profiles of miRNAs/siRNAs and their target genes in nonembryogenic and embryogenic tissues of 'Valencia' sweet orange. By high-throughput sequencing (HTS) of small RNAs and RNA degradome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
84
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(96 citation statements)
references
References 64 publications
12
84
0
Order By: Relevance
“…Auxin/ARF-related functions can also be postulated for miR390 , which had a significantly modulated expression in SE of Arabidopsis (present study) and of other plants (Zhang et al, 2012; Lin and Lai, 2013; Wu et al, 2015). miR390 has been documented as controlling the auxin signaling pathway by triggering the production of tasiARFs which down-regulate expression of ARF2, ARF3 , and ARF4 genes (Allen et al, 2005; Williams et al, 2005).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Auxin/ARF-related functions can also be postulated for miR390 , which had a significantly modulated expression in SE of Arabidopsis (present study) and of other plants (Zhang et al, 2012; Lin and Lai, 2013; Wu et al, 2015). miR390 has been documented as controlling the auxin signaling pathway by triggering the production of tasiARFs which down-regulate expression of ARF2, ARF3 , and ARF4 genes (Allen et al, 2005; Williams et al, 2005).…”
Section: Discussionsupporting
confidence: 55%
“…Similar to the widely documented involvement of miRNA molecules in plant development in vivo (Jin et al, 2013), the expression of miRNAs was reported during in vitro induced SE in several plant species including Citrus sinensis, Dimocarpus longan, Gossypium hirsutum, Larix kaempferi, Larix leptolepis, Liriodendron tulipifera × L. chinense, Manihot esculenta , and Zea mays (Zhang et al, 2012, 2014; Li et al, 2013; Lin and Lai, 2013; Yang et al, 2013; Chávez-Hernández et al, 2015; Wu et al, 2015; Lin et al, 2015a,b; Khatabi et al, 2016). Thus, the engagement of miRNAs in the embryogenic transition that is induced in vitro is assumed, although knowledge about the function of the specific miRNA in SE induction is very limited.…”
Section: Introductionmentioning
confidence: 99%
“…(Yang et al, 2013), Dimocarpus longan Lour. (Lin and Lai, 2013; Lin et al, 2015a,b) and Citrus sinensis (Wu et al, 2011; Wu X. M. et al, 2015). The same miRNA may participate in different stages of SE in different plants.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the fundamental molecular events that trigger SE could guide the improvement of propagation protocols, especially, for plants that are recalcitrant to in vitro culture (Mahdavi-Darvari et al 2015). Additionally, SE is a potential model system for studying the basis of developmental reprogramming among higher eukaryotic organisms (Zimmerman 1993;Lin and Lai 2013;Wu et al 2015), further highlighting the importance of investigating this unique developmental pathway.…”
Section: Introductionmentioning
confidence: 99%